PERAN TAHFIZD DALAM PELESTARIAN DAN PENGAJARAN HADIS (TINJAUAN HISTORIS DAN KONTEMPORER) - Siregar, Idris; Aisyah, Nur (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This study examines the role of tahfizd in the preservation and teaching of hadith, focusing on historical and contemporary reviews. Hadith, as one of the main sources of Islamic teachings after the Qur'an, requires an effective method of preservation to ensure its authenticity and accuracy. Tahfizd or memorisation has long been the main method of hadith preservation, but adaptation to the times and technology has become an important issue in the modern context. This research method used a qualitative approach that included a literature study. The literature study was conducted by reviewing various classical texts and academic sources related to tahfizd and hadith. The data collected was analysed thematically to identify important patterns in the evolution of methods of tahfizd and hadith preservation. The findings of the study show that tahfizd continues to play an important role in hadith preservation in both historical and modern contexts. Historically, tahfizd has ensured accurate transmission of traditions through generations in a consistent and reliable manner. In the contemporary era, although digital technology offers new methods of hadith transmission and preservation, challenges such as inaccuracy of information and adaptation of teaching methods still need to be overcome. This study identifies that the integration of tahfizd with modern technologies, such as digital applications, can increase the effectiveness of hadith preservation but still requires monitoring and adjustments to remain in line with the principles of authentic hadith preservation.